A EXPERIÊNCIA DIPLOMÁTICA DE JURACY MAGALHÃES: A POLÍTICA EXTERNA BRASILEIRA APÓS 1964 E A ASSINATURA DOS TRATADOS DE LISBOA: Dossier “Ditadura Militar no Brasil” (Contenciosa, 2018)
This article aims to analyze Juracy Magalhães performance in ministery of External Relations, position that exercised among January 1966 through March 1967. Its role will be analyzed in the process of redefining Brazil's foreign policy after 1964. Arising therefrom, your relationship with the United States will be highlighted, because this is considered fundamental to explain your posture ahead of the planning, coordination and execution of the Brazilian  diplomacy. These elements will be all discussed starting from a case study that possesses a synthesis potential, because in him they appear the main referring subjects to the Brazilian foreign policy in the decade of 1960. For so much, will be analyzed a series of agreements that were firm among the two countries, represented by ministers Juracy Magalhães, Brazilian chancellor and Franco Nogueira, the Portuguese congener, in September of 1966.
Keywords: Military dictatorship; foreign policy; Juracy Magalhães; Economy